EFFECTIVENESS OF INTERACTIVE METHODS IN THE ENGLISH CLASSES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In the realm of language learning, the significance of interactive methods cannot be overstated. When it comes to mastering a language like English, effective communication involves not just understanding vocabulary and grammar but also the nuances of expression and cultural context. Affective interactive methods play a pivotal role in fostering a conducive learning environment where students feel engaged, motivated, and empowered to express themselves confidently. In this article, we delve into the realm of affective interactive methods and their profound impact on English language lessons.